'Vaccies Go Home!': Evacuation, Psychoanalysis and Fiction in World War II Britain. Issue 2 (December 2016) - Ellmann, Maud
Abstract : On September 1 1939 the British government launched a program ominously codenamed Operation Pied Piper, whereby thousands of children were evacuated from the cities to the countryside. This operation brought class conflict into the foreground, laying bare the drastic inequalities of British society, but also provided the foundations for the development of child psychoanalysis. This essay examines the impact of the evacuation crisis on psychoanalytic theories of the child, comparing these to the depiction of children in wartime fiction.